The Effectiveness of Using Edmodo as a Supplementary Tool in Learning English: The Students’ Perceptions - Wahyudi, Agus (UNIVERSITAS TRIDINANTI PALEMBANG, 2016)
ABSTRACT: The use of technology in the learning process created a new concept in IT based learning, known as e-learning. In e-learning, there was a lot of online learning that can be selected by the teachers as a media of learning, such as Edmodo. Edmodo is primarily a tool for within-class communication, but also provides several ways for teachers to connect with other teachers. This research focused on investigating the effectiveness of using Edmodo as a supplementary tool in learning English from the students’ perspective. The researcher used triangulation approach in gathering data. Survey questionnaire adapted from Enriquez (2014) was used as the main research instrument of the research. 39 students joined the Edmodo class, but there were only 28 students filled the questionnaire completely. The results showed on the statement regarding the usefulness of reference materials posted by the teacher in Edmodo, a significant number 46.4% agree and 46.4% strongly agree or considered the reference materials as vital in understanding the course better. Participants also perceived that Edmodo is a good learning tool to supplement face to face discussion. One disadvantage in using Edmodo as perceived by 21.4% of the participants is the difficulty procedure to understand and to follow for them. Overall, the findings affirmed that majority of the participants considered it as an effective supplementary tool in learning English. Keywords: effectiveness, supplementary tool, English, perception